PS-C29-10: WEIGHT GAIN IS ASSOCIATED WITH INCREASED ARTERIAL STIFFNESS IN HIGH-RISK PREGNANT WOMEN. (January 2023) - Bourgeois, Sophia; Phan, Kim; Labos, Christopher; Messidi, Amira El; Abenhaim, Haim; Gagnon, Robert; Daskalopoulou, Stella S
Abstract : Objective: There have been increasing efforts to establish effective screening tools for preeclampsia in early pregnancy. Arterial stiffness is a composite indicator of vascular health, reflects endothelial dysfunction, and has been shown to be predictive of cardiovascular events in the general population, while it has been noted to be increased at the time for preeclampsia. Pregnancy is characterized by acute weight gain. However, whether pregnancy weight gain can affect arterial stiffness is not known. Therefore, we aimed to investigate the impact of pregnancy weight gain on arterial stiffness in high-risk pregnant women. Design and method: In this prospective longitudinal cohort study, pregnant women (n = 177) in their first trimester (10–13 weeks gestation) who met established clinical criteria for high-risk of preeclampsia were recruited from obstetrics clinics. Arterial stiffness measurements and weight were recorded every 4 weeks throughout pregnancy. Arterial stiffness was measured non-invasively using the validated tonometry-based SphygmoCor System. Results: Continuous variables were analyzed using linear. Analysis adjusted for maternal age showed that an increase in total pregnancy weight gain was significantly associated with increased arterial stiffness during pregnancy (0.213 [95%CI: 0.007, 0.068], p < 0.02). More specifically, an increase in late pregnancy weight gain, from second to third trimester, was significantly associated with an increase in arterial stiffness during pregnancy (adjusted beta: 0.052 [CI: 0.002, 0.102], p < 0.05). Conclusion: An increase in total pregnancy weight gain and more specifically late pregnancy weight gain is associated with an increase in arterial stiffness. This is important as arterial stiffness could be a predictive tool for preeclampsia in clinical practice.